Colombia trade analysis: European Union trade from the use of foreign trade indicators - Torres Franco, Michael (Unidad Editorial UPTC, 2020)
Commercial integration has allowed to increase economic, social, and cultural interdependence of nations; allowing this to offer more and better consumption possibilities, as well as increase the supply of production. The effects are varied and depend on the economies that negotiate, as well as on the goods and services involved. This article analyzes bilateral foreign trade based on indicators of commercial position, formulas that take data from exports and imports to determine the degree of dependence that a country has with another market, showing in this case that Colombia has a high dependence on the European market and in certain primary products; leaving as conclusion and pressing need the diversification of the exportable offer to minimize future risks. Keywords: economic integration, bilateral trade, indicators, export, import JEL Codes: C02, F14, F15, F53 Received: 24/10/2016. Accepted: 10/02/2020.  Published: 27/04/2020